Bullying the public broadcaster: Threatening the ABC's role - Quentin Dempster (Asia Pacific Network, 2004)
Public broadcasting in Australia has been under sustained attack for around 18-years now, both politically and through reduced funding. Although the Fraser Government (1975-1983) enacted legislation converting the ABC from the old broadcasting commission into a corporation (with its own borrowing and corporate treasury powers), the then Malcolm/Fraser/Doug/Anthony Liberal/National Coalition Government did not seem to hold more than the usual superficial grudges about our current affairs programmes' treatment of some  of their practitioners.